The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.2147/dddt.s236216
|View full text |Cite
|
Sign up to set email alerts
|

<p>Regulations of miR-183-5p and Snail-Mediated Shikonin-Reduced Epithelial-Mesenchymal Transition in Cervical Cancer Cells</p>

Abstract: Background: Shikonin, the main ingredient of Lithospermum erythrorhizon, has been reported to have antitumor effects via multiple targets and signaling pathways. However, the detailed mechanism underlying the effects in cervical cancer still remained unknown. Methods: MTT, wound-healing, transwell assays and flow cytometry experiments were used to measure cell growth, migration, invasion, and cell cycle analysis. Western blot was used to examine protein levels of Snail, Vimentin and E-cadherin. The expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…In consideration of the important role EMT played in cancer metastasis, we supposed whether the anti-metastasis effect of SHK was mediated by regulating the process of EMT. Therefore, in this study, we confirmed that TNBC cells acquired the epithelial phenotypes and lost the mesenchymal feature with the treatment of SHK, which was in accordance with the previous studies in cervical and lung cancers 18 , 19 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In consideration of the important role EMT played in cancer metastasis, we supposed whether the anti-metastasis effect of SHK was mediated by regulating the process of EMT. Therefore, in this study, we confirmed that TNBC cells acquired the epithelial phenotypes and lost the mesenchymal feature with the treatment of SHK, which was in accordance with the previous studies in cervical and lung cancers 18 , 19 .…”
Section: Discussionsupporting
confidence: 92%
“…SHK has been found to exert anti-cancer effects by inducing apoptosis and inhibiting proliferation, metastasis and drug resistance of cancer cells in various malignancies including breast cancer [15][16][17]. Of particular interest, it is reported that the EMT process might be a target of SHK in reducing metastasis in some cancers, such as cervical and lung cancer [18,19]. However, the effect of SHK on TNBC cells and its underlying mechanism is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…In consideration of the important role EMT played in cancer metastasis, we supposed whether the antimetastasis effect of SHK was mediated by regulating the process of EMT. Therefore, in this study, we confirmed that BC cells acquired the epithelial phenotypes and lost the mesenchymal feature with the treatment of SHK, which was in accordance with the previous studies in cervical and lung cancers [15,16].…”
Section: Akt Is Involved In the Inhibition Of Shikonin On Cancer Cellsupporting
confidence: 92%
“…SHK has been found to exert anti-cancer effects by inducing apoptosis and inhibiting proliferation, metastasis and drug resistance of cancer cells in various malignancies including breast cancer [12][13][14]. Of particular interest, it is reported that the EMT process might be a target of SHK in reducing metastasis in some cancers, such as cervical and lung cancer [15,16]. However, the effect of SHK on TNBC cells and its underlying mechanism is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…E-cadherin, the most common EMT protein, plays an important role in tumor invasion, and the loss of E-cadherin expression promotes tumor and EMT. In the cervical cancer cell lines HeLa and C33a, Shikonin inhibits EMT by inducing miR-183-5p expression via E-cadherin ( 61 ). Similarly, miR-17-5p expression was upregulated in triple-negative breast cancer.…”
Section: Active Ingredients Of Chinese Medicine Targeting Mirna Inhibmentioning
confidence: 99%